Relationship between hand grip strength and peak VO2 in community‐dwelling elderly outpatients. Issue 1 (1st January 2018) - Sugie, Masamitsu; Harada, Kazumasa; Takahashi, Tetsuya; Nara, Marina; Ishikawa, Joji; Tanaka, Jun; Koyama, Teruyuki; Fujimoto, Hajime; Obuchi, Shuichi; Kyo, Shunei; Ito, Hideki
Abstract: Background: Hand grip strength and peak oxygen uptake (VO2 ) are important components of frailty. However, the relationship between these two variables among community‐dwelling elderly people is still unclear. The present study aimed to investigate this relationship. Methods: Participants were 190 Japanese community‐dwelling elderly outpatients (61 men and 129 women, mean age 78.0 years). Hand grip strength of participants' was measured using a Smedley‐type hand dynamometer. Peak VO2 levels were assessed with a cardiopulmonary exercise test. Skeletal muscle mass index (SMI) and usual walking speed were assessed physiologically and physically. Sample size was calculated using G*Power 3.1.9.2. Results: There were significant correlations between hand grip strength and age (r = −0.22), peak VO2 (r = 0.40), SMI (r = 0.51), and usual walking speed (r = 0.29). There were significant differences in age, peak VO2 and SMI after participants were divided into normal and low hand grip strength groups according to the Asian Working Group for Sarcopenia threshold, whether both sexes were combined or considered separately. Multiple logistic regression analysis showed that peak VO2, SMI and age were independent determinants of hand grip strength after adjusting for potential confounders (Exp(B) = 0.871; 0.475; 1.065). Longitudinal analysis after 6 months of exercise training showed the percentage of change in hand grip strength and peak VO2 were correlated positively (r = 0.22) for 92 participants. Conclusion: Peak VO2 is independently associated with hand grip strength among community‐dwelling elderly outpatients.